Editorial design digital and print - Caldwell, Cath; Zappaterra, Yolanda (London Laurence King Publishing, 2014)
"Editorial Design: Digital and Print is a comprehensive guide to the traidtional and digital skills that a designer will need for a future career in visual journalism today--the design of magazines and newspapers for a wide variety of markets."--From back cover.
Includes index.
Keywords: Magazine design; Graphic design (Typography)